The influence of nonlinear effects on the spectral efficiency of multiinput antenna systems - Vishniakova, Ju. V. (Technology and design in electronic equipment, 2015)
The analysis technique and design algorithm are proposed for multiinput antenna systems, based on the mathematical model developed. The technique and algorithm described allow the analysis of a wide class of multiinput systems, in particular, MIMO systems, reconfigurable multiantenna systems, multiinput systems with nonlinear components and devices. The paper presents numerical analysis results of the intermodulation interference effect on the spectral efficiency of a multiinput system with nonlinear elements in receiving antennas, obtained using the methods, algorithms and software products developed. It is shown that in the nonlinear system intermodulation interferences appear, and the spectral efficiency of the data transmission system decays near the operating frequency due to the appearance of additional combinational components in the frequency response of the system. This effect depends on the degree of nonlinearity, radiated power, the level of interfering signals. Based on the results obtained, it was concluded that the presence of nonlinear elements and devices must be taken into account in the design and analysis processes of multiinput multiantenna systems, considering the specific types of those nonlinearities.